Spatio-temporal variations and impacting factors of vegetation NPP in the Junggar Basin, China - Tuersun, Aierken; Rusuli, Yusufujiang; Maitudi, Miriayi; Alimu, Kadiayi (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
The Junggar Basin investigated in this study has seen significant land cover and climate change. However, the spatiotemporal relationship between net primary productivity (NPP) and environmental factors remain unclear. Thus, we applied trend analysis and correlation methods to investigate the spatiotemporal characteristics of NPP and its relationship with driving factors using remotely sensed data and measured climate data from 2000 to 2015. During the study period, high values of NPP mainly occurred in the forests of the mid-elevation mountain areas. The NPP values showed an increasing trend in the different vegetation types, most likely due to climate change in combination with other factors. The annual trend of NPP in the study area varied in the range from –12.4 to 11.3 g C m–2 a–2. The desert area exhibited no significant trends, but most of the mountain areas showed a significantly increasing trend. NPP was significantly correlated with temperature and precipitation. The dominant factor affecting NPP was temperature, mainly in the Ili river watershed and the Tien Shan mountain range. However, human activity and land cover changes were also important factors affecting the fluctuations in NPP. The results of this study highlight the need for appropriate land-use strategies for managing vegetation resources in arid land ecosystems.